Using robots to help fight infectious diseases (Eurasian Research Bulletin, 2022)
As the coronavirus emergency exploded into a full-blown pandemic in early 2020, forcing countless businesses to shutter, robot-making companies found themselves in an unusual situation. We cover both the advantages and the challenges for each robot, finding that robotics systems are overall apt solutions for dealing with many of the problems brought on by COVID-19, SARS-CoV-2, Ebola virus, including: diagnosis, screening, disinfection, surgery, telehealth, care, logistics, manufacturing.